Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fmicb.2020.01610
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of an IncFIIk Plasmid Co-harboring blaIMP–26 and tet(A) Variant in a Clinical Klebsiella pneumoniae Isolate

Abstract: Carbapenems and tigecycline are two important classes of antimicrobial agents to treat the infections caused by Enterobacterales. Here, we reported a plasmid carrying both bla IMP−26 and tet(A) variant in clinical Klebsiella pneumoniae KP-1572. MIC results showed that K. pneumonia KP-1572 was resistant to a wide range of antimicrobials. The bla IMP−26 and tet(A) variant were located on an identical plasmid, which was indicated by S1-PFGE and southern blotting hybridization and can be successfully transferred b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
(39 reference statements)
3
11
0
Order By: Relevance
“…The FII plasmid pIMP-KP-13-9 was 112,209 bp long with an average GC content of 51.19% and encoding 138 predicted ORFs ( Figure 1B ). This plasmid showed 98.94% nucleotide identity and 84% query coverage with pIMP1572 (MH464586), a plasmid carrying both bla IMP – 26 and tet(A) variants ( Yao et al, 2020 ). Different from the plasmid pIMP1572, a Tn 1721 -like transposon structure carrying the tet (A) variant which is responsible for tigecycline was absent in pIMP-KP-13-9.…”
Section: Resultsmentioning
confidence: 99%
“…The FII plasmid pIMP-KP-13-9 was 112,209 bp long with an average GC content of 51.19% and encoding 138 predicted ORFs ( Figure 1B ). This plasmid showed 98.94% nucleotide identity and 84% query coverage with pIMP1572 (MH464586), a plasmid carrying both bla IMP – 26 and tet(A) variants ( Yao et al, 2020 ). Different from the plasmid pIMP1572, a Tn 1721 -like transposon structure carrying the tet (A) variant which is responsible for tigecycline was absent in pIMP-KP-13-9.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, tet (A) mutation occurring under selective pressure may lead to tigecycline treatment failure. Zhang et al (2019) reported the coexistence of mcr-1 and the tet (A) variant on the same plasmid from a K. pneumoniae isolate in human gut, and Yao et al (2020) also reported an IncFII plasmid co-harboring bla IMP– 26 and tet (A) variant in a clinical K. pneumoniae isolate. It seems that tet (A) mutants can not only occur in bla KPC– 2 -carrying plasmids, but also form fusion plasmids with other carbapenem resistance genes and mcr gene, which will cause a higher transmission risk of simultaneous resistance to carbapenem, colistin and tigecycline.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple types of tet (A)-bearing plasmids were retrieved from the NCBI GenBank database, and circular comparison analysis revealed that they have some similar structures, suggesting that genetic exchange and recombination among different types of tet (A)-bearing plasmids have occurred ( Ribera et al, 2003 ; Szmolka et al, 2015 ; Yao et al, 2020 ). In the three tet (A)-bearing plasmids obtained in this study, one class 1 integron containing multiple ARGs, including tet (A), was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetical pKpQIL_019 protein gene was identified on plasmid pKpQIL next to the Tn4401 transposon between the transposase and resolvase genes [ 60 , 61 ]. The Tn4401 transposon has also been identified in other plasmids [ 56 ], specifically in the plasmid IncFIIK [ 62 , 63 ], IncN [ 64 ] and ColE [ 65 , 66 ], IncI2 [ 67 , 68 ], and IncX3 [ 69 , 70 ]. A thorough analysis of the pKpQIL sequences in the BLAST databases revealed that the p019 sequence responsible to produce the cleavage product of the hypothetical pKpQIL_019 protein was always identified in the bla KPC gene.…”
Section: Resultsmentioning
confidence: 99%